HUBUNGAN PROTEIN KLOTHO (α-KLOTHO) DENGANSTADIUM PENYAKIT GAGAL GINJAL KRONIK SEBUAH SYSTEMATIC REVIEW - Ahmad Syarif Shahab (2020)
Background: Chronic Kidney Disease is a degenerative disease that occurs in the kidney, it is a condition where the kidney can not do it's normal function such as filtrating and reabsorbing body fluid, marked by decreased GFR value, proteinuria, and increased urea and creatinine value. Some researches has been researching about α-klotho and it's role in the organ system such as genitourinaria and cardiovascular. In some of those researches, it has been found about the role of α-klotho in CKD progression, and it's potential to be the new biomarker of CKD. The purpose of this research is to gather the findings in some of those researches and reviewing about the relationship between α-klotho and CKD stages. Method: Systematic Review with literature search using PubMed and Science Direct database. Literatures about CKD, α-klotho, and association. Result: There have been 4 researches with findings about the α-klotho value in CKD patients from stage 1 to stage 5, and it shows that α-klotho values decreased along with the escalation of CKD stages. There have been 3 researches with findings about the positive correlation between α-klotho with CKD stages and eGFR. Conclusion: The findings showed that there's a correlation between α-klotho and CKD stages.